PENGARUH PENANAMAN MODAL ASING, PENANAMAN MODAL DALAM NEGERI, DAN EKSPOR TERHADAP PERTUMBUHAN EKONOMI PAPUA - Sasno Mahurisal; Mohammad Amin; Junaidi Junaidi (e_Jurnal Ilmiah Riset Akuntansi, 2018)
ABSTRACTPerm is in this case unstable economic growth. Investments and exportsare one of the components needed to build an economic process. The researchgoals known are the methods, the domestic approach and vice versa. The type ofresearch in this study is associative research. Although the process used in thisstudy is quantitative. This research variable consists of independent variables,namely PMA, PMDN and Export Papua. Although the independent variable iseconomic growth.Collect data using secondary information from the Papua Central Data Centerfor 2010-2016. Data was analyzed using multiple linear regression analyzes by ftest and t-test using classical assumptions.The results of the study show that PMA, PMDN and Export simultaneously have asignificant impact on Papua's economic growth. The percentage of FDI does nothave a significant impact on economic growth, while PMDN and exports have apositive impact on economic growthKeywords: investment, export, economic growth